2020
DOI: 10.5194/nhess-20-3315-2020
|View full text |Cite
|
Sign up to set email alerts
|

What controls the coarse sediment yield to a Mediterranean delta? The case of the Llobregat River (NE Iberian Peninsula)

Abstract: Abstract. The human pressure upon an alluvial river in the Mediterranean region has changed its riverine and deltaic landscapes. The river has been channelized in the last 70 years while the delta has been retreating for more than a century (a set of data unknown, so far). The paper concentrates on the fluvial component, trying to connect it to the delta evolution. Is the channelization responsible for the delta retreat? We develop a method to compute the actual bed load transport with real information of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
3
Order By: Relevance
“…These observed geomorphic alterations therefore indicate a change in the sedimentary continuity and connectivity at this point (Fryirs, 2013; Wohl, 2017). Since sediment load‐carrying capacity is proportional to the alluvial width, bed slope and discharge (Martín‐Vide et al, 2020), the observed decrease in active channel width (Figure 9b) indicates a reduction in sediment load, which, under natural conditions, should tend to increase downstream (Mueller & Pitlick, 2005; Pitlick et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These observed geomorphic alterations therefore indicate a change in the sedimentary continuity and connectivity at this point (Fryirs, 2013; Wohl, 2017). Since sediment load‐carrying capacity is proportional to the alluvial width, bed slope and discharge (Martín‐Vide et al, 2020), the observed decrease in active channel width (Figure 9b) indicates a reduction in sediment load, which, under natural conditions, should tend to increase downstream (Mueller & Pitlick, 2005; Pitlick et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Per últim, s'ha utilitzat el càlcul del volums erosionat a la llera després de la crescuda extraordinària de l'any 2000 obtingut per la comparació de perfils longitudinals (Martín-Vide et al, 2020), i la dada de transport en suspensió del Llobregat (Liquete et al, 2009), per tal de comparar la magnitud del transport sòlid de les grans crescudes respecte al corresponent a un any mitjà i per a validar els valors estimats de capacitat de transport sòlid de fons.…”
Section: Transport Sòlid De Fons Del Riuunclassified
“…La crescuda del juny de l'any 2000 amb una punta de 1.500 m 3 /s es va produir just després de la construcció del dic esquerre (segona autopista) l'any 1998. Comparant el perfil longitudinal del riu un cop finalitzades les obres amb una batimetria immediatament posterior a la crescuda s'obté un volum erosionat a la llera de ≈ 125 × 10 3 m 3 /any als trams de la vall (1-3) (Martín-Vide et al, 2020). Tot aquest volum, com a mínim, va ser transmès cap al delta (4-5) i finalment a la costa.…”
Section: Paper De Les Grans Crescudesunclassified
“…Channels respond to such changes through upstream-and downstream-migrating aggradation and incision waves (An et al, 2019;Chowdhury et al, 2023;De Vriend, 2015;Y. Lin et al, 2023;Martín-Vide et al, 2020;Madej & Ozaki, 1996). Depending on the magnitude and spatial extent of the change, channel response may develop over centuries and extend over hundreds of kilometers (e.g., Simon & Rinaldi, 2006;Surian & Rinaldi, 2003;Yang et al, 2018;Ylla Arbós et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%